Securing Muslim Children’s Civil Rights: Debate on State Legal Policy towards The Issuance of Family Cards for Unregistered Marriage Couples - Fakhria, Sheila; Mustofa, Kholifatun Nur; Ma’mun, Mohamad; Wahidi, Ahmad; Rachmatulloh, Mochammad Agus (El-Mashlahah, 2024)
The government, in ensuring children's identity rights, has issued a policy regarding the issuance of family cards for unregistered marriages. This policy facilitates access to birth certificate registration for children from unregistered marriages. However, in practice, the implementation of this policy has sparked issues among judges and marriage registrars. The research was to analyze the debates surrounding the state legal policy on the issuance of family cards for couples in unregistered marriages in an effort to protect the civil rights of Muslim children. The study was an empirical legal research with a socio-legal approach. Primary data was obtained from legal officials from the KUA and religious courts in Kediri to describe the debates surrounding this regulation, which were then analyzed using the theory of contestation. The findings of this study indicated that children's rights in Islamic families include administrative rights as citizens and inherent rights as members of the Muslim family. The policy regulating the issuance of family cards for couples in unregistered marriages has become a polemic among Islamic legal officials, such as religious court judges, headmen, and KUA officials because it is seen as conflicting with the established Islamic family marriage rules in Indonesia. The meeting point between the two has not yet fully matured, as Islamic legal officials seek clearer regulations, emphasizing that couples in nikah siri should immediately conduct isbat nikah at the Religious Court.